Pengaruh Karakteristik Perusahaan, Tata Kelola, dan Faktor Lingkungan terhadap Pengungkapan Lingkungan - Adelia, Tara; Wahyuningrum, Indah Fajarini Sri (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to examine the effect of firm size, environmental audit, gender diversity, board independence, environmental performance, and pollution level on environmental disclosure. The research problem is motivated by the persistent variation in the level of environmental information disclosure among firms, despite increasing regulatory pressure and growing stakeholder demands. The theories used in this study are legitimacy theory and stakeholder theory. The novelty of this study lies in the inclusion of profitability and leverage as control variables and its focus on specific manufacturing subsectors, namely basic materials, industrials, consumer cyclicals, and consumer non-cyclicals, within the context of an emerging market. This study employs secondary data obtained from the annual reports and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Panel data regression with a fixed effect model is applied as the analytical method. The research population consists of 150 firms, with a final sample of 18 companies and a total of 54 firm-year observations selected using purposive sampling. The indicators used to measure environmental disclosure are the GRI 300 standards, consisting of 20 items. The results indicate that firm size has a positive and significant effect on environmental disclosure, a coefficient value of 0.945 with a probability value of 0.019 (< 0.05), while the other variables do not exhibit significant effects. This study is subject to limitations related to the relatively small sample size, therefore, future research is recommended to expand the sample coverage, include additional industry sectors, and apply more comprehensive measurement methods.